Heusler alloy-based heat engine using pyroelectric conversion for small-scale thermal energy harvesting. (15th April 2021) - Lallart, Mickaël; Yan, Linjuan; Miki, Hiroyuki; Sebald, Gaël; Diguet, Gildas; Ohtsuka, Makoto; Kohl, Manfred
Abstract: As an alternative to thermoelectric generators, heat engines show great interest thanks to their ability to convert temperature spatial gradient into time-domain temperature variations or vibrations. To this end, MultiPhysic Memory Alloys (MPMAs), combining shape memory characteristics with ferromagnetic properties, provide significant attractive characteristics such as sharp transition with reduced hysteresis as well as magnetic properties enabled by heating, thus allowing easier device development and implementation. In this study, we report the development of a heat engine for small-scale energy harvesting where the MPMA transfers its heat to a pyroelectric element that provides thermal to electrical energy conversion, yielding a more direct energy conversion path compared to conventional electromechanical heat engines. Furthermore, thermally decoupling the pyroelectric element from the MPMA allows a faster cooling of the latter, accounting for higher variation frequency. Compared to the use of electromagnetic transduction through a coil attached to the moving MPMA, this approach is shown to provide 3 to 9 times more power density (according to considered volume), with theoretical potential gains from 8 to 25 with the use of nonlinear electrical interfaces. Graphical abstract: Highlights: A heat engine using MultiPhysic Memory Alloy (MPMA) and pyroelement is presented. Magnetothermal coupling allows converting gradient to time-domain variations. Heat is transferred from MPMA to pyroelement for direct electrothermal conversion. Power density is increased by factors from 3 to 10 compared to similar heat engines. Enhancement possibilities are based on better thermal path and electrical interface.